The Early Bronze IVB Painted Simple Ware from Tell Shʻaīrat: an integrated archaeometric approach. (3rd May 2020) - Mouamar, Georges
Abstract : The site of Shʻaīrat is located at the western edge of the Syrian steppe (Badiyat al-Sham), 34 km south-east of the city of Homs. The preliminary results of the Syrian archaeological mission carried out at Shʻaīrat, show that it was a genuine town occupied during the mid to late 3rd millennium BC. Our results evidenced that from its foundation around 2500 BC the city was structured according to a regular, circular plan, laid out around a concentric network of streets. Tell Shʻaīrat is a key-site for understanding the dynamics of urbanization in Syria, as well as the origin of an early territorial state, on the margins of the Syrian Desert within a context of territorial conquest. In fact, EB IVB Tell Shʻaīrat may well be the largest city dated to that period thus far discovered in Western Syria. In this study, which is based on the analysis of the pottery remains recovered from Tell Shʻaīrat, typological and stylistic approaches are successfully combined with the results stemming from recent petrographic and chemical analyses of these pottery samples, in order to understand the modalities of production and distribution. This combination made it possible to identify three major pottery traditions, which correspond to different productions. This in turn made it possible to distinguish between vessels that were imported to Shʻaīrat and those that were manufactured locally. As a result of this investigation it was possible to recognize different workshops inside the polity and trace inter-regional interactions within the Badiyah region and to reconstruct the networks of exchange in which Tell Shʻaīrat was involved during the second part of the 3rd millennium BC.